Analysis of the half-life ‘ageing-constant’ theory for galvanic anodes: Analysing the model’s predictive power for CPT anodes - Stone Christian; Carr Warren; Roberts Adrian (MATEC Web of Conferences)
Over the last 4 years, an empirical model describing the current from galvanic anodes has been released based on limited data from some galvanic anodes. The model describes how the current from these anodes appears to halve over set time intervals. This ‘ageing constant’ has been used to design anode systems based on a minimum current requirement for protection and broadly applied to other galvanic anode systems. This is a radical change from the responsive behaviour model of corrosion management typically applied to galvanic anodes where the effect of the anodes was more typically tested using methods such as visual inspection, steel potentials and steel corrosion rates. In this work, we will break down the hypotheses behind this model; from the minimum current threshold being the same for all galvanic anode systems, ignoring the current spread from different anode placements, and the predictive power of this model, using data from a system cited by these authors from a Concrete Preservation Technologies Ltd (CPT) hybrid anode system. The authors of the half-life model utilised the first 7 years of data to generate an ageing constant. Now, with over 17 years of data, the model will be assessed and dramatically different conclusions drawn on the effectiveness of this model for predicting the life of CPT anodes.